Peningkatan Rofesionalisme Guru Melalui Sistem Kaderisasi - Meylani Hamid (STAI Ma'had Aly Al-Hikam Malang, 2021)
The professional attitude of a teacher is no longer reflected at this time. Where they only carry out the task of transferring knowledge without providing direction and guidance that helps the development process of each student. The purpose of this research is to build and provide efforts to develop and improve the professional attitude of a teacher by carrying out a regeneration system with a recruitment process for every new cadre who wants to apply as a teacher. The method used in this research is a qualitative method with a literature study type approach. Where the researchers compared the results of several previous findings. From the results of this study it can be concluded that the principal has a very important role in using this regeneration system. Where the principal must always motivate the teachers. With the provision of motivation and enthusiasm, teachers will feel that they are getting an award in work performance.